Lateral cleft lip and macrostomia: Case report and review of the literature - Milind Joshi; Sharad Khandelwal; Bhavesh Doshi; Sadhna Samvatsarkar (Wolters Kluwer Medknow Publications, 2014)
Lateral clefts are rare in occurrence. The lateral cleft is cause by failure of fusion of the maxillary and mandibular dermatomes. It is also associated with preaurical tags. We present a case of a lateral cleft of the lip with multiple bilateral preauricular tags that was repaired using triangular flaps.